Experimental study on piles as settlement reducers in model piled rafts - Ng, Edmund Jun Yao. (2012)
Shallow foundation such as raft will be a suitable and economical option to support the entire structure when its loading is not excessively large. This is only possible if competent soils are found near the ground surface. Although raft foundation may meet the requirement of bearing capacity easily, it tends to settle excessively and exceed the serviceability requirement. As such, piled raft foundation was first introduced by Burland et al. (1977) mainly to reduce the settlement to within allowable range, based on the introduction of composite foundation made up of a raft and some piles by Davis and Poulos (1972). This would allow the foundation to meet both stability and serviceability requirements.